Virtual Queuing: Designing a service addressing queuing problems at an amusement park - FRANZÉN, FELIX; STENING, HELENA (My University, 2018)
Extensive waiting time at amusement parks has proven to be one of the most negative factors for the guest experience. This master thesis project aims to study how the user experience of queuing at amusement parks can be improved through becoming more meaningful, pleasurable or efficient. The amusement park Liseberg in Gothenburg, Sweden, is the focus of the thesis project, alongside a Virtual queuing service. The project is conducted in collaboration with Liseberg AB and The Techno Creatives. A thorough design process has been applied to this project. Initially, several research methods and data analysis tools were used to identify problem areas within the amusement park domain. Subsequently, an ideation phase was conducted to develop potential solutions to the identified problem areas. Finally, a Virtual queuing service was prototyped, evaluated, and improved through an iterative process. Utilizing a Research through design approach, the project produced two results: a set of recommendations highlighting factors to consider when designing a virtual queuing service for amusement parks, and a prototype of a Virtual queuing service applied at Liseberg.
Keywords: virtual queues; amusement park; experience-centric service; queuing system; Liseberg; ride attractions; waiting time; user experience; service design